The sense of loss in the narratives of residents of a social welfare home - Dubas, Elżbieta; Sztobryn-Bochomulska, Justyna; Agnieszka Gralak (Difficult situation in biographies: Volume 9, 2025)
The article is devoted to the analysis of the experiences and feelings of the oldest generation of women living in a social welfare home in Poland, with particular emphasis on the sense of loss as a key element of their everyday life. Using the qualitative method, the author analyzed seven interviews to understand how the experience of loss shapes existential difficulties, the sense of meaning in life and the identity of the residents of the social welfare home. The analysis of the research material allowed us to distinguish key areas of loss, such as loss of health and fitness, limitations of social space in the dimension of the loss of loved ones, friends and place of residence. The way in which the participants of the study experienced these losses and their impact on the quality of life of senior women was also described. The article presents the specificity of life of the oldest generation, showing how existential difficulties define the everyday life of the elderly and shape their life perspective.